A Spatial Econometric Analysis of Land Use Efficiency in Large and Small Municipalities - Gianni Guastella; Stefano Pareglio; Paolo Sckokai (Fondazione Eni Enrico Mattei (FEEM), 2017)
We estimate the relationship between urban spatial expansion and its socio-economic determinants in Lombardy, the most urbanised region of Italy (and one of the most urbanized of the European Union), at the municipality level. Test results suggest that this relationship varies significantly among municipalities of different size and findings support the hypothesis that larger ones are more efficient in managing land take. In particular, we find that the marginal land consumption per new household is inversely related to the size of the municipality and we link this evidence to the fact that, since more space is often available, small municipalities pay less institutional attention to the issue of land take and consequently internalise less the environmental externalities. This evidence calls for a reflection on the role of planning policies and the effectiveness of undifferentiated measures to contain land take, especially in the case of Italy, where the municipalities, more than 99% of which have less than 50,000 inhabitants, decide on land use transformations.
Keywords: O18; Q15; R14; 330; Land Take; City Size; Threshold Regression; Spatial Econometrics